Pelatihan Pembuatan Catatan Keuangan Sederhana Pada Nelayan Budidaya Rumput Laut Kelurahan Mangkang Kota Semarang - Moeljono Moeljono (Universitas Teknokrat Indonesia, 2023)
In general, an economic activity has financial records in the form of financial reports. or at least make financial records simple and easy so they can be made by anyone. The goal of this simple bookkeeping is to evaluate the development of the business or to serve as a foundation for future business plans. Most of the fishermen cultivating seaweed are unable to make financial records or do bookkeeping; this is made possible because of the limited knowledge they have. Sales of seaweed culture products are also relatively small, and sales are done alone. When it is harvested, they will employ neighbors, but with freelancer status. There is no record of this activity. Money from sales or for production costs is not recorded at all, so fishermen do not know whether the economic activities they carry out generate profits or losses. The general objective of this service program is for seaweed-cultivating fishermen to be willing and able to keep simple financial records. With financial records, it is expected that fishermen can be measurable in managing the finances of seaweed cultivation results, including expenses, income, costs, and profits, starting from how to file documents and record them so that they can find out the progress of their business. The method used to achieve the objectives of this service program is training. The result obtained from this training activity is that seaweed-cultivating fishermen can increase their knowledge of making simple financial records. In conclusion, simple bookkeeping training received a positive response, and business actors gained knowledge and skills regarding new insights in running their businesses through simple financial records that are easy to apply.